(untitled) (Scientific journal of the Fergana State University, 2025)
This article discusses speech acts and the lexical means that bring them into being. First and foremost, illocutionary verbs were identified as lexical units representing speech acts. The distinctions between illocutionary and performative verbs are analyzed, with their differing characteristics outlined. General methods such as observation, analysis, and synthesis, alongside specific linguistic, synergetic, and hermeneutic analysis methods, were applied to examine over 100 illocutionary verbs.